Advancing Diversity, Equity and Inclusion: Strategies and Initiatives in the Workplace by IT companies like TCS & Infosys (International Journal of Food and Nutritional Sciences, 2022)
Organizations these days are prioritizing Diversity, Equity and Inclusion (DE&I) efforts as this diverse workgroup can prove to be a boon to their business. A diverse workforce calls for the need for having effective DE&I strategies and policies. This is exactly the point where the need arises for the organizations to come up with effective and innovative ideas and strategies to treat the workforce fairly and include them in the organization’s culture. This research aims to study the concepts of diversity, equity and inclusion respectively and why they are important factors at workplace. It also focuses on developing and managing diversity, equity and inclusion strategies and throws light upon the initiatives undertaken by companies thriving in IT sector like Tata Consultancy Services (TCS) and Infosys Ltd. to promote diversity, equity and inclusion in their organization.